Effect of integrated nutrient management on sustainable quality leaf production in mulberry (Morrus alba) under irrigated, alluvial soil conditions - SETUA, G C; SETUA, M; GHOSH, M; DEBNATH, S; DUTTA, A K; BANERJEE, N D; SARKAR, A (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during 2003-2005 at Berhampore (West Bengal), under irrigated Gangetic alluvial soil conditions, to study the effect of integrated nutrient packages on soil status, growth characters, leaf yield, leaf quality, N, P and K uptake by leaves in 3-year-old recommended diploid ’Si ’ and ’S 1635’ mulberry (Monts alba L.) genotypes separately utilizing 2 types each of organic manure (vermicompost and farmyard manure) and biofertilizers (Azotobacter chroococcum Beyerinck and Glomus mosseae (T.H. Nicolson & Gerd.) Gerd. & Trappe, green manuring with sunnhemp (Crotalaria jurzcea L.), 3 levels each of N, P and K in combination, spraying of a-naphthyl acetic acid (NAA) mixed micronutrients with 2 types each of different height of pruning (at ground level and 15 cm) and system of irrigation (flood and alternate furrow). Significant differences were observed among the treatments for all the parameters studied. Season x treatment interaction was found significant for plant height, N uptake and total soluble protein content in leaves of both ’S 1’ and ’S 1635’. While branches /plant, leaf area, leaf moisture and total chPorophyll content in leaves of ’S I ’, and leaf yield, K uptake and total soluble sugar content in leaves of ’S 1635’ were also significant. Further, the year x treatment interaction was also found significant for branches 1 plant, P and K uptake by leaves and total soluble protein content in leaves of both ’S 1’ and ’S 1635’, while plant height and N uptake by leaves in ’S 1635’. However, plant height, branches 1 plant, leaf area, N, P and K uptake by leaves in both ’5 1’ and ’S 1635’ and leaf yield in ’S 1’ were found almost at par owing to application of recommended dose of farmyard manure and N, P and K (control). Some of the important growth and yield parameters recorded the maximum values in different treatment combinations and the leaf quality was significantly increased in all the treatments over control